The effect of contouring the connecting bar in an acrylic-pin external fixator - Herndon, G. D.; Egger, E. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
This studies the effects of contouring of acrylic column when placed in axial compression. Six different angles were studied, 0°, 30°, 45°, 60°, 90° and a 90° with a 2.0 mm connecting bar. Each column was then placed under axial compression using a biomechanical testing machine. As the angle of the contour increased there was a significant decrease in the ultimate stiffness and ultimate strength of the columns. However, the amount of force required to cause catastrophic failure in any of the group was still high (stiffness 300 N/mm ± 70, ultimate strength 1032 N ± 139) which may not be reached in a physiological setting. When using a severe angulation of the column the using of a connecting bar will significantly increase both stiffness and strength of the acrylic.
Keywords: Acrylic; strength; stiffness